2004
DOI: 10.1590/s1516-93322004000100009
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of tetrahydrofuran lignans in Virola surinamensis

Abstract: The labelled substrates phenylalanine and phenylpropanoid Eisoeugenol were incorporated to 5-methoxy-4-O-methyl-Eisoeugenol (E-isoelemicin) and to the tetrahydrofuran lignan verrucosin in plantlets of Virola surinamensis (Myristicaceae).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
(11 reference statements)
0
1
0
1
Order By: Relevance
“…And isoeugenol synthase 1 (PhIGS1) was shown to use coniferyl acetate and NADPH as substrates to form E -isoeugenol ( Koeduka et al, 2006 ). Previously, Lopes et al had revealed that E -isoeugenol was converted to a furan lignan verrucosin in Virola surinamensis through stable-isotope labeling and in vivo feeding experiment ( Lopes et al, 2004 ). And there are indeed furan lignans (chicanine and d-epigalbacin) in S. chinensis ( Liu et al, 1981 ; Hancke et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…And isoeugenol synthase 1 (PhIGS1) was shown to use coniferyl acetate and NADPH as substrates to form E -isoeugenol ( Koeduka et al, 2006 ). Previously, Lopes et al had revealed that E -isoeugenol was converted to a furan lignan verrucosin in Virola surinamensis through stable-isotope labeling and in vivo feeding experiment ( Lopes et al, 2004 ). And there are indeed furan lignans (chicanine and d-epigalbacin) in S. chinensis ( Liu et al, 1981 ; Hancke et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…O hidrogênio vicinal é retirado do aminoácido dando origem ao ácido trans-cinâmico (Esquema 4.4) (Wightman et al, 1972). Estudos biossintéticos mostram a incorporações com L-[2-13 C]-fenilalanina em várias lignanas como, por exemplo, na Eisoelemicina (0,02-0,8%) e verrucosina (0,09-0,012%) em Virola surinamensis e na sesamina (0,11%) e sesamolina (0,16%) em Sesamun indicum (Kato et al, 1998;Lopes et al, 2004 (Davin et al, 2003;Vassao et al, 2006). Diversos estudos biossintéticos mostraram baixos níveis incorporação do ácido cinâmicos e ácido ferúlico em lignanas como no caso da podofilotoxina, em plantas jovens (2 a 3 anos) de Podophyllum hexandrum.…”
Section: Preparação Dos Derivados De áCidos Cinâmicos E Estirenosunclassified